2020
DOI: 10.3390/v12040420
|View full text |Cite
|
Sign up to set email alerts
|

KSHV ORF59 and PAN RNA Recruit Histone Demethylases to the Viral Chromatin during Lytic Reactivation

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) causes multiple malignancies in immunocompromised individuals. KSHV primarily establishes a lifelong latency in infected humans during which only a subset of viral genes is expressed while most of the viral genome remains transcriptionally silent with condensed chromatin. However, during the lytic phase, the viral genome undergoes dramatic changes in chromatin landscape leading to a transcriptionally active state with the expression of most of the viral genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…2), we revealed that PAN RNA can carry up to 5 m 6 A sites. These modifications localize within PAN RNA secondary structure motifs that we have previously shown to display low SHAPE and low Shannon entropy (12), which are characteristic of biologically significant RNA motifs (94)(95)(96)(97). We noted that PAN m 6 A status is dynamic and changes during the progression of KSHV replication, achieving the highest level during the late lytic stages.…”
Section: Discussionmentioning
confidence: 59%
“…2), we revealed that PAN RNA can carry up to 5 m 6 A sites. These modifications localize within PAN RNA secondary structure motifs that we have previously shown to display low SHAPE and low Shannon entropy (12), which are characteristic of biologically significant RNA motifs (94)(95)(96)(97). We noted that PAN m 6 A status is dynamic and changes during the progression of KSHV replication, achieving the highest level during the late lytic stages.…”
Section: Discussionmentioning
confidence: 59%
“…In our study, we provide the first comprehensive insight into the m 6 A status of KSHV-encoded PAN RNA, the key regulator of viral lytic reactivation ( Rossetto et al 2013 ; Withers et al 2018 ; Hiura et al 2020 ). Using two independent mapping approaches, that is, the 4SedTTP RT with next-generation sequencing and direct RNA sequencing, we revealed that PAN RNA can carry up to 5 m 6 A sites.…”
Section: Discussionmentioning
confidence: 99%
“…This process might operate as a fine-tuning mechanism, coordinating the function and biology of PAN RNA, as it has been demonstrated for other transcripts ( Liu et al 2015 ; Park et al 2019 ; Zhou et al 2019 ; Lee et al 2020 ). PAN RNA is a highly multifunctional transcript involved in the interactions with viral ( Rossetto et al 2013 ; Campbell et al 2014a ) and cellular proteins the ( Rossetto and Pari 2012 ), modulating the chromatin and episomal DNA state during viral lytic reactivation ( Strahan et al 2017 ; Hiura et al 2020 ), and facilitating the nuclear export of late viral mRNAs ( Withers et al 2018 ). The dynamic m 6 A modifications to PAN RNA might provide the means to orchestrate its functions with the immediate need of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Polyadenylated nuclear (PAN) RNA, a highly-expressed non-coding KSHV lytic RNA, facilitates interaction between ORF59, histone demethylases ubiquitously transcribed tetratricopeptide repeat X chromosome (UTX) and Jumonji-domain-containing 3 (JMJD3), and the viral genome. The subsequent reduction in H3K27 trimethylation, particularly at the ORF50 promoter, promotes robust lytic gene expression [ 98 , 99 ]. Conversely, KSHV lytic protein K8 acts as a modulator of KSHV lytic reactivation by recruiting HDACs to the RTA promoter to repress transcriptional activity, potentially serving as a brake on runaway lytic activity [ 100 ].…”
Section: Mechanisms Regulating Kshv Reactivation From Latencymentioning
confidence: 99%